Pathologic characterization of canine multiple system degeneration in the Ibizan hound. Issue 1 (January 2022) - St. Jean, Samantha C.; Jortner, Bernard S.; Doan, Ryan N.; Dindot, Scott V.; Johnson, Gary S.; Bullock, Garrett; Whitley, Derick B.; Levine, Jonathan M.; Hancock, Sandra K.; Ambrus, Andy; Porter, Brian F.
Canine multiple system degeneration (CMSD) is a progressive hereditary neurodegenerative disorder commonly characterized by neuronal degeneration and loss in the cerebellum, olivary nuclei, substantia nigra, and caudate nuclei. In this article, we describe 3 cases of CMSD in Ibizan hounds. All patients exhibited marked cerebellar ataxia and had cerebellar atrophy on magnetic resonance imaging. At necropsy, all cases showed varying degrees of cerebellar atrophy, and 2 cases had gross cavitation of the caudate nuclei. Histologic findings included severe degeneration and loss of all layers of the cerebellum and neuronal loss and degeneration within the olivary nuclei, substantia nigra, and caudate nuclei. Pedigree analysis indicated an autosomal recessive mode of inheritance, but the causative gene in this breed is yet to be identified. CMSD resembles human multiple system atrophy and warrants further investigation.